CATECHOL-O-METHYLTRANSFERASE VAL158MET GENE POLYMORPHISM IN SCHIZOPHRENIA RISPERIDONE-TREATED PATIENTS - Fitri N. Ramadhani; Ajeng Diantini; Shelly Iskandar; Melisa I. Barliana (Fakultas Farmasi, Universitas Padjadjaran, 2020)
Catechol-O-Methyltransferase (COMT) gene is located at chromosome 22q11 on a location with a high risk of the occurrence of schizophrenia that has a role in the degradation and inactivation of dopamine neurotransmitters. The COMT Val158Met gene polymorphism has enzymatic activity variation that can affect the availability of COMT enzyme, balance of dopamine level, and availability of dopamine receptors so it can influence the effectiveness of risperidone therapy that varies. The aim of this study was to observe the genetic profile of COMT Val158Met gene polymorphism and its correlation with effectiveness of risperidone therapy either single or combination in schizophrenia patients at Mental Hospital of Prof. Dr. Soerojo Magelang. This study was an observational descriptive study with a cross-sectional plan. Data collection was carried out prospectively through assessment of risperidone therapy effectiveness based on PANSS-EC scores in medical record, whole blood sampling, and identification of COMT Val158Met gene polymorphism using Polymerase Chain Reaction-Amplification Refractory Mutation System (PCR-ARMS) method. The result of study showed that all schizophrenia patients at Mental Hospital of Prof. Dr. Soerojo Magelang had heterozygote Val/Met (GA) genotype. Combination risperidone therapy was the most widely used (90.79%) rather than single with the result that 44 patients of 69 patients (63.77%) responded to the combination risperidone. Combined risperidone clozapine therapy was the most widely used (57.97%) with the result that 23 patients out of 40 (57.50%) responded to the combination therapy.